Gestures’ Contribution to Collective Metaphorical Thinking in a Community of Philosophical Inquiry (CPI) - POLO, Claire (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Gestures’ Contribution to Collective Metaphorical Thinking in a Community of Philosophical Inquiry (CPI). This paper explores an idea expressed by a student discussing where our thoughts come from: to think we have to move our hands. Such sentence echoes the literature on the role of gesture for thinking. This study also focuses on the collective advancement of reasoning in a CPI. The instructor chooses to conclude by asking each student to suggest an analogy of thinking. This closing sequence reveals how the instructor, through metaphorical gestures, fosters collective awareness of new propositions, and their further elaboration. After characterizing the cognitive models so produced, video analysis is used to follow their collective, verbal and gestural construction along the discussion.